2013
DOI: 10.1590/s0034-737x2013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Composite synthetic hydroxyapatite 30%, in two physical states, as dermal filler

Abstract: RESUMO Compósito de hidroxiapatita sintética 30%, em dois estados físicos, como preenchedor de relevo cutâneoObjetivou-se avaliar a resposta tecidual, após implantação de hidroxiapatita sintética 30% (HAP-91 ® ), em dois estados físicos, para preenchimento cutâneo. Foram utilizados 18 coelhos da raça Nova Zelândia, distribuídos aleatoriamente em dois grupos ® fluida e viscosa) e, posteriormente, divididos em três subgrupos, de acordo com o período pós-implante, em oito, 21 e 49 dias. Em cada grupo foi implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
4
0
4
Order By: Relevance
“…This tissue had characteristics of an active tissue, rich in fibroblasts and blood vessels (hyperemia in varying degrees). These findings are characteristic of the normal reaction of the organism when in contact with an implant, prosthesis, or biomaterial [53], and were also observed by Carlo et al [36], who observed fibroblast proliferation and formation of fibrous tissue around HAp particles implanted in subcutaneous tissue of dogs and by Sepúlveda et al [50], when implanting HAp in subcutaneous tissue of rabbits. In the HCoγ 1 sample, this fibrous tissue appeared to be more organized, tending to encapsulate the material.…”
Section: In Vivo Biocompatibilitysupporting
confidence: 74%
See 3 more Smart Citations
“…This tissue had characteristics of an active tissue, rich in fibroblasts and blood vessels (hyperemia in varying degrees). These findings are characteristic of the normal reaction of the organism when in contact with an implant, prosthesis, or biomaterial [53], and were also observed by Carlo et al [36], who observed fibroblast proliferation and formation of fibrous tissue around HAp particles implanted in subcutaneous tissue of dogs and by Sepúlveda et al [50], when implanting HAp in subcutaneous tissue of rabbits. In the HCoγ 1 sample, this fibrous tissue appeared to be more organized, tending to encapsulate the material.…”
Section: In Vivo Biocompatibilitysupporting
confidence: 74%
“…The postoperative observations indicated a good acceptance of the compounds, since macroscopically no inflammatory reaction was observed and no rejection of the implanted compounds occurred as well. Carlo et al [ 36 ], Yanagida et al [ 49 ], and Sepúlveda et al [ 50 ] obtained similar results in their studies with Hap associated with bioglass, HAp covering lactic acid, and synthetic HAp for skin filling, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Sepulveda et al [ 48 ] evaluated synthetic hydroxyapatite HAP-91 ® as a dermal filler; they showed that this intradermal implant tends to encapsulate itself and does not cause signs of toxicity but only presents an initial inflammatory response.…”
Section: Resultsmentioning
confidence: 99%